Control of Flow Past an Airfoil Section Using Rotating Cylinders - Nazari, Argin (2015)
A Master of Science thesis in Mechanical Engineering by Argin Nazari entitled, "Control of Flow Past an Airfoil Section Using Rotating Cylinders," submitted in January 2015. Thesis advisor is Dr. Saad Ahmed and co-advisor is Dr. Essam Wahbe. Available are both soft and hard copies of the thesis.